Sistem Informasi Stok Barang Pada PT. Graha Mentari Infinit - Mahdiyana; Meri Hendayani; Muhamad Burhanudin; Thoyyibah T. (CV. Multi Kreasi Media, 2022)
The rapid development of technology has a positive impact on the smoothness and convenience of humans in carrying out various activities. The process of technological development will continue to move forward and be faster and more accurate in making decisions. In the current era of globalization, advances in existing technology, the company has a role in the development of technology that is very fast and precise. Computerized systems have become a daily necessity and cannot be separated to produce information. Information is a basic need in an agency company and Hospitality is no exception. Current computer technology is very supportive in carrying out data processing to create information that is used in order to get good results and maximum performance. Sanctuary Spaces by Twospaces (Hospitality and Offices) is located on Jl. Wijaya Kusuma No. 2 Jati Pulo Palmerah, West Jakarta 11460. Still doing the calculation of stock items manually so that information errors often occur. This resulted in the management of the stock of goods not running effectively and could even harm the company. The inventory information system is designed with the prototype method,with the prototype method the design can be done in a shorter time. This system is built using the PHP language with the help of a MySQL database.